Legal Issues of Health Frontier in Two Countries: Challenges from Indonesia and Singapore - Murdi, Patria Bayu; Rahimah Embong (Lembaga Contrarius Indonesia, 2024)
Foreign medical personnel are needed to overcome the challenges of a shortage of medical personnel. However, the current issue lies in the ineffective regulations governing foreign medical personnel in Indonesia, which hinder the country's ability to enhance its health services. This research aims to conduct a comparative study with Singapore, which has superior health services, to examine the use of foreign medical personnel in improving the quality of health services in Indonesia. This research uses normative juridical research, employing a conceptual, statutory, and comparative approach. The research results show that, first, the utilization of foreign medical personnel in Indonesia has not been able to improve the quality of health services in Indonesia due to weaknesses in legal structure in the supervision and licensing process, the substance of regulations that do not yet provide legal protection and the condition of the Indonesian people who are not yet able to use such personnel foreign medical. Second, the Singapore government's mechanism for utilizing foreign medical personnel is easy and successful. Singapore strategically utilization foreign medical personnel to meet its healthcare needs. In addition, foreign medical personnel have several rights, including a basic salary and monthly allowances, health insurance, and income tax, which are not deducted from their pay. Therefore, Indonesia needs to adopt a policy system that is not limited to lex generalis but also becomes a guide that provides certainty in law enforcement and is not just a reference or boundary line for derivative regulations.